Tinjauan Hukum Jual Beli Pakaian Bekas Impor Di Tugu Pahlawan Kota Surabaya - Faizatul Adibah (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The purpose of this study was to describe the buying and selling of imported used clothing in Tugu Pahlawan Surabaya according to the review of Trade Law No. 7 of 2014 and Fiqh Muamalah. This study was called empirical legal research by using a conceptual approach and statute approach. Focus of this research was conducted at the Tugu Pahlawan Surabaya by doing interviews to buyers and sellers of imported used clothing and going into the field to observe the buying and selling process of imported used clothing in Tugu Pahlawan Surabaya, after and then it was analyzed by Trade Law No. 7 of 2014 and Fiqh Muamalah. The results indicated that; 1) the buying and selling of imported used clothing in Tugu Pahlawan Surabaya was contrary to the Trade Law No. 7 of 2014 article 47 which stated that